Prognostic tools in palliative care: a scope review - Alyni Sebastiany Mendes Ferreira; Lucas Soares Brito; Letícia Arrais Rocha; Beatriz Morais Costa; Felipe Silva Ribeiro; João Batista Santos Garcia (BrJP)
BACKGROUND AND OBJECTIVES: The uncertainty of death’s exact timing necessitates accurate survival predictions for better end-of-life care. This study was to map and guide the use of prognostic tools in palliative care (PC), despite the lack of comprehensive comparisons. The objective of this study was to identify the available evidence of the validated Prognostic Survival Scales used in patients in PC. CONTENTS: A scope review was performed using the Joanna Briggs Institute method, with PCC methodology (population, concept, and context) in the Excerpta Medica Database (EMBASE), Medline (via EMBASE), Cumulative Index to Nursing and Allied Health Literature (CINAHL) Plus with Full Text, Latin American Literature in Health Sciences (LILACS) and SCO-PUS. The review covered 504 studies published between 1999 and 2020, of which 40 remained after three selection stages. The study presents 13 different tools found and their prognostic factors in table form and characterize them one by one. The PPI (Palliative Prognostic Index) scale was present in 52.5% of the studies, appearing in the highest number of publications. CONCLUSION: This scope review shows a still small number of studies related to prognostic tools in PC, in particular, addressing other life-threatening diseases, making it difficult to build international policies, as well as demonstrating their cost-benefit and effectiveness. The large number of different prognostic factors makes each scale more indicated and effective depending on the scenario, confirming the need for research to evaluate the applicability and effectiveness of these, not only in one, but in several different environments and situations.